A Comparison of 4Csâ€™ Praxis in Two Recommended English Textbooks For senior high school in Indonesia - Try Oktaviani Shalehah; Tedi Rohadi; Zakky Yavani (IAIN Syekh Nurjati Cirebon, 2020)
This study aims to know the 4Cs skills, as a mandatory principal of curriculum 2013, in two English Textbooks which used as references in teaching and learning process for eleventh grade. The two English Textbooks studied are â€œBahasa Inggrisâ€ and â€œContextual Englishâ€. This research used content analysis as a method, to get the data the researcher use document analysis. After analyzing, the data were interpreted, compared and reported. The research finding shows that 4Cs skills from both English Textbooks are included on its package of activities; 1) pre activities, 2) content of the materials, and 3) worksheets. The critical thinking aspects are mostly found on its pre-activity and contents, while communicative and collaborative aspects sometimes emerge on both. The worksheet requires creativity of the students as well as communicative and collaborative aspects on it. It was also found that among two English Textbooks studied, the 4Cs aspects on â€œContextual English Textbooksâ€ are shown up more frequent than â€œBahasa Inggrisâ€ text book.